THE EFFECT OF WORK-FAMILY CONFLICT ON EMPLOYEE PERFORMANCE WITH JOB STRESS AS A MEDIATING VARIABLE AT ARIA GAJAYANA HOTEL IN MALANG CITY - Chairain Octaviana; Rifki Hanif (Jurnal Ekonomi Manajemen dan Bisnis, 2025)
This research investigates the effect of work family conflict on employee performance, with work stress serving as a mediating factor, all within the context of the hospitality sector at the Aria Gajayana Hotel in Malang. The subject matter is pertinent because employees in the hospitality industry frequently encounter intense workloads and unpredictable scheduling, which elevate the probability of role conflict and psychological distress. This research aims to answer the question of how work-family disagreement leads to elevated job strain and reduced staff output, and whether job strain serves to mediate the connection between the two. This study provides empirical data concerning the mediating role of job strain in the relationship between work-family disagreement and staff output within the Indonesian hospitality industry, a sector that remains insufficiently explored in this particular high-demand occupational setting. A quantitative methodology utilizing Partial Least Squares Structural Equation Modeling (PLSSEM) via SmartPLS 3 was utilized. Data were gathered from 54 personnel through saturated sampling and analyzed via measurement and structural model assessments to determine direct and indirect consequences. The results demonstrate that work family conflict substantially increases work stress and concurrently diminishes employee performance. Work stress also holds a significant negative impact on employee performance and operates as an intermediary factor in the pathway between work family conflict and employee performance. The study concludes that role conflict and job strain are central determinants influencing staff output in the hospitality sector. These findings underscore the importance of organizational assistance, equitable task distribution, and stress management tactics to sustain peak performance.